The Use Of An Inclined Mat To Improve The Learning Outcomes Of Fifth-Year Pupils At State Primary School In The Forward Roll Skills - Arbian Rafly Sugiarto; Donny Anhar Fahmi; Tubagus Herlambang (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
This study aims to determine whether the use of an inclined mat can improve the learning outcomesof fifth-year pupils at State Primary School 02 Babadan in the forward roll skill. The research wasmotivated by low learning outcomes, particularly in the psychomotor and affective domains, aswell as the lack of varied teaching media in physical education. A quantitative approach with aquasi-experimental method and a one-group pretest-posttest design was employed. The populationconsisted of all 17 fourth-year pupils, selected through saturated sampling. Data were collectedthrough cognitive, affective, and psychomotor tests. Descriptive analysis showed an increase inaverage scores across all domains. The paired t-test results indicated no significant improvement inthe cognitive domain (p = 0.136), but a significant improvement in the affective domain (p = 0.015).The Wilcoxon signed-rank test revealed a significant improvement in the psychomotor domain (p= 0.002), with 13 pupils showing increased scores. In conclusion, the use of an inclined mat iseffective in improving students’ affective and psychomotor learning outcomes in forward rollgymnastics, although it does not significantly affect cognitive understanding. This researchrecommends the inclined mat as an innovative and practical teaching aid for primary schoolphysical education